Serum Effects Following Tissue Thromboplastin Infusion - Astrup, T; Albrechtsen, O. K (Thrombosis and Haemostasis, 1969)
Tissue thromboplastin injected into the femoral vein of anesthetized rabbits produced intravascular clotting in the vessels through which the thromboplastin flowed. In the systemic arteries macroscopically visible clots were never observed. No trace of tissue thromboplastin could be demonstrated in blood drawn from the carotid artery following infusion of tissue thromboplastin into the femoral vein. The slight, transient enhancement of coagulation of the arterial blood following tissue thromboplastin infusion was caused by a serum effect. After intravenous injection of serum, enhanced activation of coagulation could be observed for a period of up to 2 hrs. It is concluded that tissue thromboplastin, intravenously injected, is removed from the blood during its passage from the femoral vein to the systemic arteries, probably in the capillaries of the lung. True hypercoagulability appears to be due to a serum effect or caused by partial activation of the intrinsic coagulation system. The levels of coagulation precursors in blood are of minor significance.